Retrobulbar Spot Sign Predicts Thrombolytic Treatment Effects and Etiology in Central Retinal Artery Occlusion. Issue 8 (August 2015) - Nedelmann, Max; Graef, Michael; Weinand, Frank; Wassill, Klaus-Heiko; Kaps, Manfred; Lorenz, Birgit; Tanislav, Christian
<x xml:space="preserve">Abstract</x> Background and Purpose— Transorbital sonography may help establish diagnosis of central retinal artery occlusion (CRAO). Next to Doppler sonographic proof of CRAO, an intra-arterial spot sign can be detected in some cases. We hypothesized that it reflects calcified components. It may be associated with embolization from atherosclerotic plaques and may negatively influence thrombolysis. Methods— Prospective monocenter study of 46 patients with ophthalmologically confirmed CRAO. Systemic tissue-type plasminogen activator thrombolysis was performed when appropriate. All patients received etiologic workup. Results— CRAO was confirmed by Doppler in all patients. Fifty-nine percent of patients with arterio-arterial embolization were spot sign–positive compared with 20% from cardiac source (P<0.05) and none with vasculitis. Eleven patients underwent thrombolysis. Clinically relevant visual improvement was only found in absence of a spot sign (P<0.05). Conclusions— Transbulbar ultrasound is valuable for initial diagnosis and diagnostic workup of CRAO. In the light of inconsistent results of previous thrombolysis trials, ultrasound may identify patients more likely to benefit from thrombolytic treatment.